2022
DOI: 10.1111/jfpp.16465
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer‐based antimicrobial coatings for aquatic food products: A review

Abstract: Aquatic food products, including fish and crustaceans, are some of the most consumed foods globally and are highly prone to microbial contamination. Such products have been preserved using conventional processing techniques such as freezing, cold storage, modified atmospheric packaging (MAP), and vacuum packaging. However, these techniques have been used since decades and are not cost‐effective. Therefore, alternative sustainable strategies need to be explored. One viable option is the application of biopolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 159 publications
0
10
0
Order By: Relevance
“…Shi et al (2019) found that dodo ice coating significantly reduced fat and protein oxidation in frozen shrimp and that the addition of rosemary extract to the ice coating solution was more effective. Biodegradable packaging materials and antimicrobial agent-based coating systems are also attracting attention for their ability to retain the integrity quality of aquatic products (Chakraborty et al, 2022;Rathod et al, 2023). Liu et al (2021b) investigated the effect of bioactive coatings combined with gas-regulated packaging on the oxidation and degradation of myogenic fibrin in cultured pufferfish and found that the treated coatings inhibited the development of carbonyl groups and maintained a high-sulfhydryl content during refrigeration, indicating a certain degree of delay in myogenic fibrin oxidation.…”
Section: Improved Packaging Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Shi et al (2019) found that dodo ice coating significantly reduced fat and protein oxidation in frozen shrimp and that the addition of rosemary extract to the ice coating solution was more effective. Biodegradable packaging materials and antimicrobial agent-based coating systems are also attracting attention for their ability to retain the integrity quality of aquatic products (Chakraborty et al, 2022;Rathod et al, 2023). Liu et al (2021b) investigated the effect of bioactive coatings combined with gas-regulated packaging on the oxidation and degradation of myogenic fibrin in cultured pufferfish and found that the treated coatings inhibited the development of carbonyl groups and maintained a high-sulfhydryl content during refrigeration, indicating a certain degree of delay in myogenic fibrin oxidation.…”
Section: Improved Packaging Methodsmentioning
confidence: 99%
“…Protein oxidation is a covalent modification process in which ROSs or secondary oxidation products act on proteins to induce structural changes, including the breaking of the protein-peptide chain backbone, crosslinking or polymerisation within and between protein molecules and modification of amino acid side chains (Dom ınguez et al, 2022). Reactive intermediates are essential for protein oxidation processes and ROSs and reactive nitrogen species (RNSs) are two common and highly sensitive reactive intermediates that can be generated in organisms through various metabolic pathways.…”
Section: Mechanism Of Protein Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 9% of all the plastics get recycled and the rest ends in the land fields and water bodies. This high production of plastics is not only a serious threat to individuals, or communities but to the whole ecosystem, especially the marine ecosystem [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%